Analysis of the Impact of Liquid Waste on Environmental Pollution - Yurnalisdel (Formosa Journal of Sustainable Research, 2022)
Lack of awareness of the importance of environmental cleanliness makes it easy to carry out random waste disposal which causes negative impacts on the environment and the living things in it. The purpose of carrying out this study is to find out the impact of liquid waste on environmental pollution. The assessment technique used in this study is a descriptive technique through a qualitative approach. In this qualitative approach, the examiner tends to use himself to be used as an instrument so that it can be used flexibly and can take clear events and interactions. The results of the analysis show that liquid waste generated from various human activities such as acquisition through household activities, industry, workshops, and others can cause serious impacts on the environment if it exceeds the quality standards that have been decided. Polluted river waters kill river biota, and the low level of health has resulted in several residents who have experienced skin diseases by stagnant water carrying waste.